Extranasopharyngeal Angiofibroma Arising from the Anterior Nasal Septum in a 35-Year-Old Woman - Kujundžić, Tarik (Craniomaxillofac Trauma Reconstr, 2019)
Angiofibroma is a relatively rare vascular lesion originating predominantly in the nasopharynx and occurs typically in male adolescents. Extranasopharyngeal sites of origin, such as nasal cavity, paranasal sinuses, pharynx, and larynx, are extremely rarely seen in clinical practice. In the nasal cavity, extranasopharyngeal angiofibromas (ENAs) have been reported to originate from the nasal septum, as well as from the middle and inferior turbinate. In this study, we report a case of a 35-year-old female patient with angiofibroma originating from the anterior part of the nasal septum with left-sided nasal obstruction and mild-to-moderate epistaxis as main complaints. After the radiological diagnostics and embolization of sphenopalatine artery, we performed the excision of the lesion with removal of small part of septal mucosa and perichondrium around the attachment of tumor pedicle. Histopathological examination suggested the presence of angiofibroma and diagnosis was confirmed by immunohistochemical analysis. This is the fifth reported case of septal ENA in female population in the English-language literature.